Identification of cholesterol binding sites in the serotonin(1A) receptor - Sengupta, Durba; Chattopadhyay, Amitabha (Journal of Physical Chemistry B, 2012)
The serotonin(1A) receptor is a representative member of the G protein-coupled receptor (GPCR) superfamily and serves as an important drug target in the development of therapeutic agents for neuropsychiatric disorders. Previous work has shown the requirement of membrane cholesterol in the organization, dynamics, and function of the serotonin(1A) receptor. We show here that membrane cholesterol binds preferentially to certain sites on the serotonin(1A) receptor by performing multiple, long time scale MARTINI coarse-grain molecular dynamics simulations. Interestingly, our results identify the highly conserved cholesterol recognition/interaction amino acid consensus (CRAC) motif on transmembrane helix V as one of the sites with high cholesterol occupancy, thereby confirming its role as a putative cholesterol binding motif. These results represent the first direct evidence for membrane cholesterol binding to specific sites on the serotonin(1A) receptor and represent an important step in our overall understanding of GPCR function in health and disease.

Cholesterol modulates the dimer interface of the beta(2)-adrenergic receptor via cholesterol occupancy sites - Prasanna, Xavier; Chattopadhyay, Amitabha; Sengupta, Durba (Biophysical Journal, 2014)
The beta(2)-adrenergic receptor is an important member of the G-protein-coupled receptor (GPCR) superfamily, whose stability and function are modulated by membrane cholesterol. The recent high-resolution crystal structure of the beta(2)-adrenergic receptor revealed the presence of possible cholesterol-binding sites in the receptor. However, the functional relevance of cholesterol binding to the receptor remains unexplored. We used MARTINI coarse-grained molecular-dynamics simulations to explore dimerization of the beta(2)-adrenergic receptor in lipid bilayers containing cholesterol. A novel (to our knowledge) aspect of our results is that receptor dimerization is modulated by membrane cholesterol. We show that cholesterol binds to transmembrane helix IV, and cholesterol occupancy at this site restricts its involvement at the dimer interface. With increasing cholesterol concentration, an increased presence of transmembrane helices I and II, but a reduced presence of transmembrane helix IV, is observed at the dimer interface. To our knowledge, this study is one of the first to explore the correlation between cholesterol occupancy and GPCR organization. Our results indicate that dimer plasticity is relevant not just as an organizational principle but also as a subtle regulatory principle for GPCR function. We believe these results constitute an important step toward designing better drugs for GPCR dimer targets.

Differential dynamics of the serotonin(1A) receptor in membrane bilayers of varying cholesterol content revealed by all atom molecular dynamics simulation - Patra, Swarna M.; Chakraborty, Sudip; Shahane, Ganesh; Prasanna, Xavier; Sengupta, Durba; Maiti, Prabal K.; Chattopadhyay, Amitabha (Molecular Membrane Biology, 2015)
The serotonin(1A) receptor belongs to the superfamily of G protein-coupled receptors (GPCRs) and is a potential drug target in neuropsychiatric disorders. The receptor has been shown to require membrane cholesterol for its organization, dynamics and function. Although recent work suggests a close interaction of cholesterol with the receptor, the structural integrity of the serotonin(1A) receptor in the presence of cholesterol has not been explored. In this work, we have carried out all atom molecular dynamics simulations, totaling to 3s, to analyze the effect of cholesterol on the structure and dynamics of the serotonin(1A) receptor. Our results show that the presence of physiologically relevant concentration of membrane cholesterol alters conformational dynamics of the serotonin(1A) receptor and, on an average lowers conformational fluctuations. Our results show that, in general, transmembrane helix VII is most affected by the absence of membrane cholesterol. These results are in overall agreement with experimental data showing enhancement of GPCR stability in the presence of membrane cholesterol. Our results constitute a molecular level understanding of GPCR-cholesterol interaction, and represent an important step in our overall understanding of GPCR function in health and disease.
Keywords: GPCR; Membrane cholesterol; molecular dynamics simulation; serotonin(1A) receptor

Molecular dynamics simulations of GPCR-cholesterol interaction: an emerging paradigm - Sengupta, Durba; Chattopadhyay, Amitabha (Biochimica Et Biophysica Acta-Biomembranes, 2015)
G protein-coupled receptors (GPCRs) are the largest class of molecules involved in signal transduction across cell membranes and represent major targets in the development of novel drug candidates. Membrane cholesterol plays an important role in GPCR structure and function. Molecular dynamics simulations have been successful in exploring the effect of cholesterol on the receptor and a general consensus molecular view is emerging. We review here recent molecular dynamics studies at multiple resolutions highlighting the main features of cholesterol-GPCR interaction. Several cholesterol interaction sites have been identified on the receptor that are reminiscent of nonannular sites. These cholesterol hot-spots are highly dynamic and have a microsecond time scale of exchange with the bulk lipids. A few consensus sites (such as the CRAC site) have been identified that correspond to higher cholesterol interaction. Interestingly, high plasticity is observed in the modes of cholesterol interaction and several sites have been suggested to have high cholesterol occupancy. We therefore believe that these cholesterol hot-spots are indicative of `high occupancy sites' rather than `binding sites'. The results suggest that the energy landscape of cholesterol association with GPCRs corresponds to a series of shallow minima interconnected by low barriers. These specific interactions, along with general membrane effects, have been observed to modulate GPCR organization. Membrane cholesterol effects on receptor structure and organization, that in turn influences receptor cross-talk and drug efficacy, represent a new frontier in GPCR research. This article is part of a Special Issue entitled: Lipid-protein interactions. Guest Editors: Amitabha Chattopadhyay and jean-Marie Ruysschaert. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Coarse-grain simulation; CRAC; GPCR; Lipid-receptor interaction; Membrane cholesterol; Receptor dimerization

Role of lipid-mediated effects in beta(2)-adrenergic receptor dimerization - Prasanna, Xavier; Chattopadhyay, Amitabha; Sengupta, Durba (biochemical roles of eukaryotic cell surface macromolecules, 2015)

Cholesterol-dependent conformational plasticity in GPCR dimers - Prasanna, Xavier; Sengupta, Durba; Chattopadhyay, Amitabha (Scientific Reports, 2016)
The organization and function of the serotonin1A receptor, an important member of the GPCR family, have been shown to be cholesterol-dependent, although the molecular mechanism is not clear. We performed a comprehensive structural and dynamic analysis of dimerization of the serotonin1A receptor by coarse-grain molecular dynamics simulations totaling 3.6 ms to explore the molecular details of its cholesterol-dependent association. A major finding is that the plasticity and flexibility of the receptor dimers increase with increased cholesterol concentration. In particular, a dimer interface formed by transmembrane helices I-I was found to be sensitive to cholesterol. The modulation of dimer interface appears to arise from a combination of direct cholesterol occupancy and indirect membrane effects. Interestingly, the presence of cholesterol at the dimer interface is correlated with increased dimer plasticity and flexibility. These results represent an important step in characterizing the molecular interactions in GPCR organization with potential relevance to therapeutic interventions.

Conformational dynamics of GPCR dimers is dependent on membrane cholesterol - Sengupta, Durba; Prasanna, Xavier; Chattopadhyay, Amitabha (Biophysical Journal, 2016)

Ganglioside GM1 interacts with the serotonin1A receptor via the sphingolipid binding domain - Prasanna, X.; Jafurulla, M.; Sengupta, Durba; Chattopadhyay, Amitabha (Biochimica et Biophysica Acta, 2016)
Glycosphingolipids are minor yet essential components of eukaryotic cell membranes and are involved in a variety of cellular processes. Although glycosphingolipids such as GM1 have been previously reported to influence the function of G protein-coupled receptors (GPCRs), the molecular mechanism remains elusive. In this paper, we have explored the interaction of GM1 with the serotonin1A receptor, an important neurotransmitter receptor that belongs to the GPCR family. To examine the molecular basis of the interaction of GM1 with the serotonin1A receptor, we performed a series of coarse-grain molecular dynamics simulations of the receptor embedded in membrane bilayers containing GM1. Our results show that GM1 interacts with the serotonin1A receptor predominantly at the extracellular loop 1 and specifically at the sphingolipid binding domain (SBD). The SBD motif consists of a characteristic combination of aromatic, basic and turn-inducing residues, and is evolutionarily conserved in case of the serotonin1A receptor. The interaction of the SBD site with GM1 appears to stabilize a 'flip-out' conformation in which W102 of the extracellular loop 1 flips out from the central lumen of the receptor toward the membrane. The population of the 'flip-out' conformation is increased in the presence of cholesterol. Our data strongly suggest that a direct interaction between GM1 and the SBD site of the serotonin1A receptor may occur in vivo. In view of the reported role of GM1 and the serotonin1A receptor in neurodegenerative diseases, GM1-receptor interaction assumes significance in the context of malfunctioning of neuronal GPCRs under such conditions.

Protein-dependent membrane interaction of a partially disordered protein complex with oleic acid : Implications for cancer lipidomics - Chaudhuri, Arunima; Prasanna, Xavier; Agiru, Priyanka; Chakraborty, Hirak; Rydstrom, Anna; Ho, James C. S.; Svanborg, Catharina; Sengupta, Durba; Chattopadhyay, Amitabha (Scientific Reports, 2016)
Bovine α-lactalbumin (BLA) forms cytotoxic complexes with oleic acid (OA) that perturbs tumor cell membranes, but molecular determinants of these membrane-interactions remain poorly understood. Here, we aim to obtain molecular insights into the interaction of BLA/BLA-OA complex with model membranes. We characterized the folding state of BLA-OA complex using tryptophan fluorescence and resolved residue-specific interactions of BLA with OA using molecular dynamics simulation. We integrated membrane-binding data using a voltage-sensitive probe and molecular dynamics (MD) to demonstrate the preferential interaction of the BLA-OA complex with negatively charged membranes. We identified amino acid residues of BLA and BLA-OA complex as determinants of these membrane interactions using MD, functionally corroborated by uptake of the corresponding α-LA peptides across tumor cell membranes. The results suggest that the α-LA component of these cytotoxic complexes confers specificity for tumor cell membranes through protein interactions that are maintained even in the lipid complex, in the presence of OA.

What can simulations tell us about GPCRs: integrating the scales - Sengupta, Durba; Joshi, Manali; Athale, Chaitanya A.; Chattopadhyay, Amitabha (G Protein-Coupled Receptors: Signaling, Trafficking and Regulation, 2016)
The functional dynamics of G protein-coupled receptors (GPCRs) encompasses multiple spatiotemporal scales, ranging from femtoseconds to seconds and Angstroms to micrometers. Computational approaches, often in close collaboration with experimental methods, have been invaluable in unraveling GPCR structure and dynamics at these various hierarchical levels. The binding of natural and synthetic ligands to the wild-type and naturally occurring variant receptors have been analyzed by several computational methods. The activation of receptors from the inactive to the active state has been investigated by atomistic simulations and ongoing work on several receptors will help uncover general and receptor-specific mechanisms. The interaction of GPCRs with complex membranes that contain phospholipids and cholesterol have been probed by coarse-grain methods and shown to directly influence receptor association. In this chapter, we discuss computational approaches that have been successful in analyzing each scale of GPCR dynamics. An overview of these approaches will allow a more judicious choice of the appropriate method. We hope that an appreciation of the power of current computational approaches will encourage more critical collaborations. A comprehensive integration of the different approaches over the entire spatiotemporal scales promises to unravel new facets of GPCR function.

Exploring GPCR lipid interactions by molecular dynamics simulations: excitements, challenges, and the way forward - Sengupta, Durba; Prasanna, Xavier; Mohole, Madhura; Chattopadhyay, Amitabha (Journal of Physical Chemistry B, 2018)
Gprotein-coupled receptors (GPCRs) are seven transmembrane receptors that mediate a large number of cellular responses and are important drug targets. One of the current challenges in GPCR biology is to analyze the molecular signatures of receptor-lipid interactions and their subsequent effects on GPCR structure, organization, and function. Molecular dynamics simulation studies have been successful in predicting molecular determinants of receptor-lipid interactions. In particular, predicted cholesterol interaction sites appear to correspond well with experimentally determined binding sites and estimated time scales of association. In spite of several success stories, the methodologies in molecular dynamics simulations are still emerging. In this Feature Article, we provide a comprehensive overview of coarse-grain and atomistic molecular dynamics simulations of GPCR-lipid interaction in the context of experimental observations. In addition, we discuss the effect of secondary and tertiary structural constraints in coarse-grain simulations in the context of functional dynamics and structural plasticity of GPCRs. We envision that this comprehensive overview will help resolve differences in computational studies and provide a way forward.

Membrane-induced organization and dynamics of the N-terminal domain of chemokine receptor CXCR1: insights from atomistic simulations - Kharche, Shalmali; Joshi, Manali; Sengupta, Durba; Chattopadhyay, Amitabha (Chemistry and Physics of Lipids, 2018)
The CXC chemokine receptor 1 (CXCR1) is an important member of the G protein-coupled receptor (GPCR) family in which the extracellular N-terminal domain has been implicated in ligand binding and selectivity. The structure of this domain has not yet been elucidated due to its inherent dynamics, but experimental evidence points toward membrane-dependent organization and dynamics. To gain molecular insight into the interaction of the N-terminal domain with the membrane bilayer, we performed a series of microsecond time scale atomistic simulations of the N-terminal domain of CXCR1 in the presence and absence of POPC bilayers. Our results show that the peptide displays a high propensity to adopt a beta-sheet conformation in the presence of the membrane bilayer. The interaction of the peptide with the membrane bilayer was found to be transient in our simulations. Interestingly, a scrambled peptide, containing the same residues in a randomly varying sequence, did not exhibit membrane-modulated structural dynamics. These results suggest that sequence-dependent electrostatics, modulated by the membrane, could play an important role in folding of the N-terminal domain. We believe that our results reinforce the emerging paradigm that cellular membranes could be important modulators of function of G protein-coupled receptors such as CXCR1.
Keywords: All atom MD simulations; beta-sheet; CXCR1; Membrane interaction; N-terminal

Molecular determinants of GPCR oligomerization - Mohole, Madhura; Kumar, G. Aditya; Sengupta, Durba; Chattopadhyay, Amitabha (Molecular determinants of GPCR oligomerization, 2020)

Role of cholesterol-mediated effects in GPCR heterodimers - Prasanna, Xavier; Mohole, Madhura; Chattopadhyay, Amitabha; Sengupta, Durba (Chemistry and Physics of Lipids, 2020)
G protein-coupled receptors (GPCRs) are transmembrane receptors that mediate a large number of cellular responses. The organization of GPCRs into dimers and higher-order oligomers is known to allow a larger repertoire of downstream signaling events. In this context, a crosstalk between the adenosine and dopamine receptors has been reported, indicating the presence of heterodimers that are functionally relevant. In this paper, we explored the effect of membrane cholesterol on the adenosine(2A) (A(2A)) and dopamine D-3 (D-3) receptors using coarse-grain molecular dynamics simulations. We analyzed cholesterol interaction sites on the A(2A) receptor and were able to reproduce the sites indicated by crystallography and previous atomistic simulations. We predict novel cholesterol interaction sites on the D-3 receptor that could be important in the reported cholesterol sensitivity in receptor function. Further, we analyzed the formation of heterodimers between the two receptors. Our results suggest that membrane cholesterol modulates the relative population of several co-existing heterodimer conformations. Both direct receptor-cholesterol interaction and indirect membrane effects contribute toward the modulation of heterodimer conformations. These results constitute one of the first examples of modulation of GPCR hetero-dimerization by membrane cholesterol, and could prove to be useful in designing better therapeutic strategies.
Keywords: Adenosine(2A) receptor; Cholesterol; Dopamine D-3 receptor; G protein-coupled receptors; Heterodimer; MARTINI coarse-grain simulation

Conformational plasticity and dynamic interactions of the N-terminal domain of the chemokine receptor CXCR1 - Kharche, Shalmali; Joshi, Manali; Chattopadhyay, Amitabha; Sengupta, Durba (Plos Computational Biology, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The dynamic interactions between G protein-coupled receptors (GPCRs) and their cognate protein partners are central to several cell signaling pathways. For example, the association of CXC chemokine receptor 1 (CXCR1) with its cognate chemokine, interleukin-8 (IL8 or CXCL8) initiates pathways leading to neutrophil-mediated immune responses. The N-terminal domain of chemokine receptors confers ligand selectivity, but unfortunately the conformational dynamics of this intrinsically disordered region remains unresolved. In this work, we have explored the interaction of CXCR1 with IL8 by microsecond time scale coarse-grain simulations, complemented by atomistic models and NMR chemical shift predictions. We show that the conformational plasticity of the apo-receptor N-terminal domain is restricted upon ligand binding, driving it to an open C-shaped conformation. Importantly, we corroborated the dynamic complex sampled in our simulations against chemical shift perturbations reported by previous NMR studies and show that the trends are similar. Our results indicate that chemical shift perturbation is often not a reporter of residue contacts in such dynamic associations. We believe our results represent a step forward in devising a strategy to understand intrinsically disordered regions in GPCRs and how they acquire functionally important conformational ensembles in dynamic protein-protein interfaces.

Synergistic and competitive lipid interactions in the serotonin1A receptor microenvironment - Mohole, Madhura; Sengupta, Durba; Chattopadhyay, Amitabha (ACS Chemical Neuroscience, 2022)
The interaction of lipids with G-protein-coupled receptors (GPCRs) has been shown to modulate and dictate several aspects of GPCR organization and function. Diverse lipid interaction sites have been identified from structural biology, bioinformatics, and molecular dynamics studies. For example, multiple cholesterol interaction sites have been identified in the serotonin1A receptor, along with distinct and overlapping sphingolipid interaction sites. How these lipids interact with each other and what is the resultant effect on the receptor is still not clear. In this work, we have analyzed lipid-lipid crosstalk at the receptor of the serotonin1A receptor embedded in a membrane bilayer that mimics the neuronal membrane composition by long coarse-grain simulations. Using a set of similarity coefficients, we classified lipids that bind at the receptor together as synergistic cobinding, and those that bind individually as competitive. Our results show that certain lipids interact with the serotonin1A receptor in synergy with each other. Not surprisingly, the ganglioside GM1 and cholesterol show a synergistic cobinding, along with the relatively uncommon GM1-phosphatidylethanolamine (PE) and cholesterol-PE synergy. In contrast, certain lipid pairs such as cholesterol and sphingomyelin appear to be in competition at several sites, despite their coexistence in lipid nanodomains. In addition, we observed intralipid competition between two lipid tails, with the receptor exhibiting increased interactions with the unsaturated lipid tails. We believe our work represents an important step in understanding the diversity of GPCR-lipid interactions and exploring synergistic cobinding and competition in natural membranes.
Keywords: GPCR; lipid crosstalk; Martini coarse-grain simulations; Membrane cholesterol; neuronal membranes

Palmitoylation of the glucagon-like peptide-1 receptor modulates cholesterol interactions at the receptor-lipid microenvironment - Naglekar, Amit; Chattopadhyay, Amitabha; Sengupta, Durba (Journal of Physical Chemistry B, 2023)
The G protein-coupled receptor (GPCR) superfamily of cell surface receptors has been shown to be functionally modulated by post-translational modifications. The glucagon-like peptide receptor-1 (GLP-1R), which is a drug target in diabetes and obesity, undergoes agonist-dependent palmitoyl tail conjugation. The palmitoylation in the C-terminal domain of GLP-1R has been suggested to modulate the receptor-lipid microenvironment. In this work, we have performed coarse-grain molecular dynamics simulations of palmitoylated and nonpalmitoylated GLP-1R to analyze the differential receptor-lipid interactions. Interestingly, the placement and dynamics of the C-terminal domain of GLP-1R are found to be directly dependent on the palmitoyl tail. We observe that both cholesterol and phospholipids interact with the receptor but display differential interactions in the presence and absence of the palmitoyl tail. We characterize important cholesterol-binding sites and validate sites that have been previously reported in experimentally resolved structures of the receptor. We show that the receptor acts like a conduit for cholesterol flip-flop by stabilizing cholesterol in the membrane core. Taken together, our work represents an important step in understanding the molecular effects of lipid modifications in GPCRs.

Probing the energy landscape of the lipid interactions of the serotonin 1A receptor - Mohole, Madhura; Naglekar, Amit; Sengupta, Durba; Chattopadhyay, Amitabha (Biophysical Chemistry, 2024)
G protein-coupled receptors (GPCRs) are lipid-regulated transmembrane proteins that play a central role in cell signaling and pharmacology. Although the role of membrane lipids in GPCR function is well established, the underlying GPCR-lipid interactions have not been thermodynamically characterized due to the complexity of these interactions. In this work, we estimate the energetics and dynamics of lipid association from coarse-grain simulations of the serotonin1A receptor embedded in a complex membrane. We show that lipids bind to the receptor with varying energetics of 1-4 kT, and timescales of 1-10 mu s. The most favorable energetics and longest residence times are observed for cholesterol, glycosphingolipid GM1, phosphatidylethanolamine (PE) and phosphatidylserine (PS) lipids. Multi-exponential fitting of the contact probability suggests distinct dynamic regimes, corresponding to ps, ns and mu s timescales, that we correlate with the annular, intermediate and nonannular lipid sites. The timescales of lipid binding correspond to high barrier heights, despite their relatively weaker energetics. Our results highlight that GPCR-lipid interactions are driven by both thermodynamic interactions and the dynamical features of lipid binding.
Keywords: GPCR-lipid interactions; Lipid energetics; Lipid residence time; Molecular dynamics simulations; Serotonin 1 a receptor

Increased cholesterol interactions in the active conformational state of the glucagon-like peptide-1 receptor - Naglekar, Amit; Chattopadhyay, Amitabha; Sengupta, Durba (Biophysical Journal, 2026)
The glucagon-like peptide-1 receptor (GLP-1R) is a class B G-protein-coupled receptor that plays an important role in metabolic regulation and consequently is a target for type 2 diabetes and obesity therapeutics. Although cholesterol has been reported to be implicated in receptor activation, its interactions with the receptor during the activation cycle have not been probed. Using coarse-grained molecular dynamics simulations, we have characterized the cholesterol interactions with GLP-1R in four conformational states: the inactive, partially active, GLP-1-bound active, and exenatide-bound active conformational states. We observed that the cholesterol hotspots vary between the receptor states with an increased enrichment of cholesterol around the receptor in the active conformational states. Importantly, more favorable interaction energetics and increased residence times of cholesterol were identified in the active conformational state of the receptor, although lower in magnitude than previously reported. Notably, subtle differences could be distinguished between the GLP-1-bound and exenatide-bound receptor, underlining the ligand-specific effects. Our findings emphasize the increased selectivity of cholesterol toward the active state of GLP-1R and highlight the role of conformational dynamics in receptor-lipid interplay. Our work helps to understand how cholesterol modulates GLP-1R, with potential effects on its role as a regulator in lipid metabolism, thereby opening avenues to leverage these lipid interactions in targeted drug therapy. SIGNIFICANCE This study provides an understanding of how cholesterol directly influences the function of GLP-1R, a key therapeutic target for metabolic diseases including type 2 diabetes and obesity. Using coarse-grained molecular dynamics simulations, we show that cholesterol binding, favorable interactions, and residence times increase when GLP-1R is in its active states. These interactions vary subtly depending on the activating ligand, highlighting ligand-specific effects. Our findings highlight the critical role of conformational dynamics in receptor-lipid interplay and suggest that understanding these cholesterol-GLP-1R interactions could pave the way for novel strategies in targeted drug therapy for metabolic disorders.

Specificity and promiscuity of phosphoinositide lipid interactions with the serotonin1A receptor: insights from submillisecond coarse-grain simulations - Nikte, Siddhanta V.; Sengupta, Durba; Chattopadhyay, Amitabha (ACS Chemical Neuroscience, 2026)
G protein-coupled receptors (GPCRs) are lipid-dependent membrane receptors that serve as important cell signaling hubs. Phosphoinositide (PIP) lipids represent an important class of anionic lipids that play vital roles in neuronal function and signaling. PIP lipids have been reported to modulate GPCR function, although the specificity and molecular details of the interactions are still not clear. An important GPCR in this context is the serotonin(1A) receptor, a neurotransmitter GPCR, which has been reported to interact with phosphatidylinositol 4-phosphate (PIP1) lipids. In this work, we computationally analyzed the specificity of the serotonin(1A) receptor-PIP lipid interactions using coarse-grain molecular dynamics simulations. Our results predict that four anionic lipid sites are present at the receptor surface, although the relative populations are dependent on the lipid type. PIP1 lipids exhibit the highest interaction at a charged cleft formed by transmembrane helices VI and VII. We observed electrostatic interactions at a cluster of charged residues (Arg341, Lys342, Lys345) and hydrophobic and aromatic interactions at residue Ile349 and Tyr402. In contrast, phosphatidylinositol 4,5-bisphosphate (PIP2) and phosphatidylinositol 3,4,5-trisphosphate (PIP3) lipids interact more with transmembrane helix IV. We observed that anionic phospholipids such as phosphatidylserine (PS) interact at these sites, although their occupancy at these sites is much reduced. By elucidating the molecular determinants of these interactions in silico, this study generates novel, testable hypotheses regarding the functional role of specific lipid-receptor contacts. Our work constitutes an important step in analyzing molecular signatures of phosphoinositide lipid-GPCR interactions in the overall context of diverse roles of phosphoinositides in neuronal function and signaling.
Keywords: anionic lipids; Cholesterol; GPCR; MARTINIcoarse-grain simulations; PIP lipids; serotonin(1A) receptor